2021
DOI: 10.3390/antiox10111709
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Infusions: Can They Be a Source of Microelements with Antioxidant Properties?

Abstract: Coffee is a beverage that is very popular all over the world. Its pro-health effect has been demonstrated in many publications. This drink can counteract the effects of oxidative stress thanks to its antioxidant properties. The aim of this study was to collect data on the content of microelements with antioxidant activity (manganese, zinc, copper, iron) in coffee infusions, taking into account various factors. The study considered publications from the years 2000–2020 found in Google Scholar and PubMed databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 111 publications
(321 reference statements)
0
10
0
Order By: Relevance
“…The main commercial coffee blends are Arabica ( Coffea arabica L.) and Robusta ( Coffea canephora Pierre ex Froehner) [ 65 ]. Its main component is caffeine, which belongs to antioxidants, and its long-term intake in large quantities reduces oxidative stress [ 66 ]. Other components of coffee beans include carbohydrates, proteins, fats, alkaloids, diterpenes, free amino acids, melanoides and minerals and both macro- and microelements [ 67 ].…”
Section: Stimulantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main commercial coffee blends are Arabica ( Coffea arabica L.) and Robusta ( Coffea canephora Pierre ex Froehner) [ 65 ]. Its main component is caffeine, which belongs to antioxidants, and its long-term intake in large quantities reduces oxidative stress [ 66 ]. Other components of coffee beans include carbohydrates, proteins, fats, alkaloids, diterpenes, free amino acids, melanoides and minerals and both macro- and microelements [ 67 ].…”
Section: Stimulantsmentioning
confidence: 99%
“…Other components of coffee beans include carbohydrates, proteins, fats, alkaloids, diterpenes, free amino acids, melanoides and minerals and both macro- and microelements [ 67 ]. Coffee contains microelements that show antioxidant effects, such as manganese, zinc, copper and iron [ 66 ]. It can also be a source of fluorine, chromium and cobalt [ 66 ].…”
Section: Stimulantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Han et al, showed that coffee brewed for 3 h contained the lowest acrylamide levels, while steeping and dripping featured the lowest furan levels after 24 h and 12 h, respectively [ 64 ]. The effect of coffee brewing on microelement composition appears conflicting though, and likely is not significantly influenced by the brewing method, warranting further studies [ 70 ]. Janda et al have reported recently that coffee beverages prepared by simple infusion and AeroPress were rich in magnesium (116.3 mg/L), manganese (0.6 mg/L), chromium (0.03 mg/L), cobalt (0.01 mg/L), and potassium (1540.7 mg/L), while the drip brew contained a valuable silicon content (3.4 mg/L) [ 71 ].…”
Section: Metabolomics Applications In Coffee Brewingmentioning
confidence: 99%
“…Two diterpenes, cafestol and kahwoel, present in coffee oil, are the main cholesterol-raising compounds in coffee; however, they are mostly removed using paper filters. Therefore, unfiltered coffee is a source of diterpenes, whereas filtered coffee does not increase serum cholesterol much [ 89 ].…”
Section: Preventionmentioning
confidence: 99%